Modulations of static and dynamic functional connectivity among brain networks by electroacupuncture in post-stroke aphasia - Xu, Minjie; Gao, Ying; Zhang, Hua; Zhang, Binlong; Lyu, Tianli; Tan, Zhongjian; Li, Changming; Li, Xiaolin; Huang, Xing; Kong, Qiao; Xiao, Juan; Kranz, Georg S.; et al. (Frontiers in Neurology, 2022)
Post-stroke aphasia (PSA) is a language disorder caused by left hemisphere stroke. Electroacupuncture (EA) is a minimally invasive therapeutic option for treating PSA. Tongli (HT5) and Xuanzhong (GB39), two important language-associated acupoints, are frequently used in rehabilitation treatment of PSA. Preliminary evidence indicates functional activation in distributed cortical areas upon HT5 and GB39 stimulation. However, research on modulations of static and dynamic functional connectivity (FC) in the brain by EA in PSA is still lacking. The aim of this study was to explore the PSA-related online effects of EA stimulation at HT5 and GB39 on neural processing. Thirty-five participants were recruited, including 19 PSA patients and 16 healthy controls (HCs). The BOLD signal was analyzed by static independent component analysis (static ICA), generalized Psychophysiological Interactions (gPPI) and dynamic independent component analysis (dyn-ICA), including age, gender, and education as covariates. Result revealed that PSA showed activated clusters in left Putamen, left postcentral gyrus (PostCG) and left angular gyrus (AG) in salience network (SN), compared to HC group. The interaction effect on static FC showed increased functional coupling between left calcarine and right lingual (F =3.16, pFDR = 0.043). For the dynamic FC, PSA patients had higher variability and frequencies of factor3, with the strongest connections between supramarginal gyrus (SMG) and posterior cingulum (F = 5.42, pFDR = 0.03), middle cingulum and postcentral gyrus (PostCG) (F = 5.27, pFDR = 0.036), triangle inferior frontal and lingual (F = 5.57, pFDR = 0.026). Dynamic FC value was anticorrelated to transcribing score, describing score, and dictating score in Chinese Rehabilitation Research Center for Chinese Standard Aphasia test (CRRCAE). These findings suggest that EA stimulation significantly modulated nodes of regions/networks involved in language network (LN), SN, cerebellar network (CN), occipital cortex, somatosensory regions and cerebral limbic system.